Serviceology for Designing the Future Selected and Edited Papers of the 2nd International Conference on Serviceology - Maeno, Takashi; Sawatani, Yuriko; Hara, Tatsunori; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book provides a useful overall guide to the state of the art in theory and practice of services. It can also serve as a reference book for researchers in various fields, including engineering, marketing, economics, and other disciplines. Advanced works presented here were selected from the proceedings of the Second International Conference on Serviceology (ICServ2014), held September 14-16, 2014. This book helps readers to understand serviceology, which tackles with a broad range of services, the globalization of the economy and also enhances the quality of life of local residents.
A Survey of Business Models in Japanese Restaurant and Retail Industries -- Employee Satisfaction Analysis in Food Service Industry - Resultant of Questionnaire to the Restaurant Staff -- Exploration of Service System and Value Co-creation Mechanism in Islamic Banking in Pakistan -- The Ordering of Fast Food Using Menu -- Evaluation of taxiing at a large airport considering customer satisfaction -- Research of the Social New Transportation Service on Electric Full Flat Floor Bus -- Analysis of business process innovation using outsourcing -- Mixed Reality Navigation on a Tablet Computer for Supporting Machine Maintenance in Wide-area Indoor Environment -- Business Structure of E-book Service as a Product Service System: A Game Theoretic Approach -- Service Field Simulator: Virtual environment display system for analyzing human behavior in service fields -- Improvement of Sharing of observations and awareness in nursing by voice tweets -- A System Promoting Cooperation Between Medicine and Dentistry Using Key Performance Indicators and Importance-Performance Analysis -- Designing the Amount of Image Delay in Tele-surgery -- Visualization of Muscle Activity during Squat Motion for Skill Education -- Extraction and Evaluation of Proficiency in Bed Care Motion for Education Service of Nursing Skill -- Exploratory Analysis on Factors of Patient Satisfaction in HCAHPS Databases -- One Cycle of Smart Access Vehicle Service Development -- The value of community for resolving social isolation -- Basic Study of Mobility of Elderly People from the Perspective of Their Emotional Value -- Workshop-based Policy Platform for Public-Private Partnership (WP5): Designing Co-Creative Policy-Making Platform for Regional Development of Nagano -- System Design of Happy Town Using Four Factors of Happiness -- Evaluation of the Productivity Improvement by Information Presentation in Surveillance Service -- Personalized Information Service Model that Reflects Individual's Will -- Ranking Smartphone Apps Based onUsers' Behavior Records -- Contribution of ICT monitoring system in Agricultural Water Management and Environmental Conservation -- A Questionnaire Assessment of the Contributing Factors to Empathy -- Evaluation of Countermeasures for Low Birthrate and Aging of the Population in a Suburban New Town -- Analysis of value co-creation between farmers and Land Improvement District in Japan through irrigation service improvement by good water quality -- Analysis of Multi-language Knowledge Communication Service in Intercultural Agricultural Support.-A Value Co-Creation Model for Multi-Language Knowledge Communication -- Field-Oriented Service Design: A Multiagent Approach.-EXPERIENCE PLOT:A Template for Co-Creating Customer Journey -- Kizashi Method:Grasping the change of future user's values.- Service Practices as Organizational Phenomena -- The Findings from the First Service Design Projects -- An Evaluation Method of a Service Business model using Wants Chain Analysis -- Design method of target customer's WANTs for a service based on classification of services using WANTs -- Business Model Generation Canvas as a Method to Develop Customer-Oriented Service Innovation -- Aligning Product-Service offerings with customer expectations -- User-De-Centeredness in Service Design -- A Probe-based Approach for Designing Inspirational Services at Museums.
Keywords: Industrial Management; Production management; Engineering design; Computer networks .; Industrial Management; Operations Management; Engineering Design; Computer Communication Networks